Persepsi Siswa Mengenai Mitigasi Bencana Gempa di SMA Negeri 1 Suwawa Timur - Lasulika, Cindy Tsasil; Melo, Ramla Hartini (Universitas Negeri Gorontalo, 2025)
This study aims to analyze students’ perceptions of earthquake disaster mitigation at SMA Negeri 1 Suwawa Timur, focusing on aspects such as understanding, attitude, preparedness, participation, and evaluation of the school’s mitigation program. A descriptive quantitative method was employed, with data collected through questionnaires completed by students. The results indicate that students' understanding of earthquake mitigation falls into the